(untitled) (Revista Científica Compendium, 2024)
Comisión Modelo Educativo UCLA: Edgar Rodríguez León, Lenny Escalona Anzola, Maritza Bracho, Erika Jerez, Giosianna Polleri, Olga Palma, Juana López y Jaqueline Viera.